1999
DOI: 10.1161/01.atv.19.8.1960
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Background Determines the Extent of Atherosclerosis in ApoE-Deficient Mice

Abstract: Abstract-Two strains of ApoE-deficient mice were found to have markedly different plasma lipoprotein profiles and susceptibility to atherosclerosis when fed either a low-fat chow or a high-fat Western-type diet. FVB/NJ ApoE-deficient (FVB E0) mice had higher total cholesterol, HDL cholesterol, ApoA1, and ApoA2 levels when compared with C57BL/6J ApoE-deficient (C57 E0) mice. At 16 weeks of age, mean aortic root atherosclerotic lesion area was 7-to 9-fold higher in chow diet-fed C57 E0 mice and 3.5-fold higher i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
135
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(146 citation statements)
references
References 65 publications
8
135
1
Order By: Relevance
“…Infected animals presented a reduction in the serum VLDL cholesterol fraction that represents an important proatherogenic lipoprotein in mice. These results agree with those obtained by Paigen et al (29), Dansky et al (6), and Grimsditch et al (19), who suggested that the correlation between blood cholesterol and atherosclerosis is not evident in cases of concomitant infection.…”
Section: Discussionsupporting
confidence: 92%
“…Infected animals presented a reduction in the serum VLDL cholesterol fraction that represents an important proatherogenic lipoprotein in mice. These results agree with those obtained by Paigen et al (29), Dansky et al (6), and Grimsditch et al (19), who suggested that the correlation between blood cholesterol and atherosclerosis is not evident in cases of concomitant infection.…”
Section: Discussionsupporting
confidence: 92%
“…While increased apoB-48 containing lipoproteins are atherogenic in the 129-apoE mice, increased HDL-cholesterol may overcome this adverse effect. The inverse relationship between elevated plasma lipids and reduced atherosclerosis has been reported previously in apoE-/-mice that have been backcrossed onto an FVB/NJ background (18). These authors analyzed an F2 population between apoE-/-mice on the FVB and B6 backgrounds, and found no correlation between the plasma levels of lipid/lipoproteins and the size of lesions at aortic root.…”
Section: Discussionmentioning
confidence: 78%
“…Different strains of mice display differential atherosusceptibility (38)(39)(40). The lesion mean area is 7-to 9-fold and 3.5-fold higher in ApoE Ϫ/Ϫ mice raised on C57BL͞6 background when fed chow and HFD, respectively, compared with ApoE Ϫ/Ϫ mice raised on FVB͞N background (39).…”
Section: Discussionmentioning
confidence: 99%
“…Different strains of mice display differential atherosusceptibility (38)(39)(40). The lesion mean area is 7-to 9-fold and 3.5-fold higher in ApoE Ϫ/Ϫ mice raised on C57BL͞6 background when fed chow and HFD, respectively, compared with ApoE Ϫ/Ϫ mice raised on FVB͞N background (39). The fact that AEBP1 TG mice were generated on FVB͞N background limits our ability to investigate a direct role of AEBP1 in the development of atherosclerosis, because mice are highly resistant to the development of atherosclerosis under normal conditions (41).…”
Section: Discussionmentioning
confidence: 99%